Challenges of endodontic treatment in cases of radix entomolaris (Research, Society and Development, 2024)
Endodontic treatment involves removing the filling material, instrumentation and filling the canal system, with the aim of achieving a better result. The radix entomolaris (RE) consists of a change in the number of roots of the lower molars. The objective of this research was to carry out an indirect and bibliographic approach to understand the challenges of endodontic treatment in cases of radix entomolaris, demonstrating the importance of the dental surgeon having dental anatomical knowledge and the need to request imaging exams before carrying out the procedure. Thus, a descriptive approach was carried out regarding endodontic treatment in cases of radix entomolaris, investigating the incidences in recent years through analysis of scientific articles. The research was carried out in a secondary format, that is, through scientific articles. Articles published on the Google Scholar, Scientific Electronic Library Online (Scielo) and Pubmed platforms were selected. Through bibliographical references, it was verified that morphological knowledge of the root canal system is essential, as well as following all stages of the treatment correctly. Achieving endodontic success, in the presence of ER, requires knowledge about its anatomy, incidence, a prior clinical evaluation, as well as overcoming possible difficulties that exist during treatment. Therefore, we consider the proposed treatment to be a successful intervention.